Implementation of the User Centered Design (UCD) Method for MSME E-commerce - Albertus Dwiyoga Widiantoro (Soegijapranata Catholic University, 2023)
Web and mobile-based application development for MSMEs is very necessary to help marketing and increase revenue. A user-centered design (UCD) approach that actively involves users at every stage of the design process for product development becomes more effective and efficient, resulting in E-commerce applications that are designed together with users to produce applications that suit the needs of local MSME users